Bond strength of debonded orthodontic brackets after different reconditioning and priming protocols: An in vitro study - Nguyen Viet Anh; Trinh Khanh Linh; Le Thi Lan Anh; Dao Ngoc Linh Chi; Nguyen Thi Thu Huong; Nguyen Thi Trang (PLoS ONE, 2026)
Introduction Although various bracket recycling methods have been studied, the combined influence of bracket reconditioning methods and primer protocols on the bonding performance of debonded orthodontic brackets remains unclear. This study aimed to evaluate the effects of three reconditioning methods and three primer protocols on the bond strength of rebonded orthodontic brackets to enamel. Materials and methods One hundred stainless steel brackets were bonded to extracted premolars and divided into 10 groups (n = 10). Ninety brackets were debonded, reconditioned using OneGloss bur, flaming, or sandblasting, and rebonded with Mani Bond, Denu Bond, or no primer. Ten new brackets served as controls. Bracket bases were examined using scanning electron microscopy (SEM). Bond strength, adhesive remnant index (ARI), and bonding reliability were evaluated using SBS testing, ARI scoring, and Weibull analysis. Results Bond strength was significantly influenced by the interaction between reconditioning method and primer protocol (p < 0.001). Sandblasting combined with Mani Bond produced the highest bond strength (9.33 ± 3.02 MPa), whereas OneGloss and sandblasting combined with Denu Bond achieved bond strengths comparable to new brackets and higher reliability, reflected by greater Weibull moduli (4.74 and 4.72). SEM demonstrated more effective mesh cleaning after sandblasting than after OneGloss bur treatment or flaming. ARI distributions differed significantly among groups (p = 0.01), with failures occurring predominantly at the bracket–adhesive interface. Conclusions The bonding performance of rebonded orthodontic brackets is influenced by the interaction between reconditioning and priming protocols. Appropriate combinations of these procedures may improve the rebonding outcome.